PSYCOEDUCATION AND IMPROVING THE ROLE OF COMMUNITY IN BREAKING THE CHAIN OF THE SPREAD OF COVID - 19 - Mandala Putra, Sabprudin; Baiti, Noor (PT Altin Riset Publishing, 2023)
World Healt Organization (WHO) has declared Covid-19 as a pandemic, based on the distribution of the virus which geographically estimates 193 countries including Indonesian. In Indonesian, the distribution of Covid-19 continues to grow. This problem is caused by the circulation of data that is sometimes a bit trustworthy (hoax), the lack of function and public awareness in cutting the Covid-19, distribution chain, and because of the implementation of health protocols. The purpose of this community service is distribute psychoeducation to the village community in the spirit of devotion and to increase the function of the community in cutting the chain of the spread of Covid-19